한국 노인자살률과 사회·경제적 요인의 관련성 -1990년~2010년 변화 추이를 중심으로 - 김형수; 권이경; Kim, Hyoung-Soo; Kwon, Lee-Kyung (한국콘텐츠학회 논문지, 13(6), 2013)
This study analyzed the relationship between elderly suicide rates and socio-economic factors from the macroscopic perspectives. As certain theoretical background of elderly suicide, sociological and economic perspectives are applied. The economic factors of elderly suicide rates consisted of economic growth and unemployment rate, economic activity rate of the aged, and relative poverty rate (income inequality rate). The sociological factors included social welfare spending, divorce rate, growth rate of population aging, and elderly dependency ratio. According to research findings, first, the more economic activity of the aged is low, the more elderly suicide rate is high. Second, the more social welfare spending rate goes flat, the more elderly suicide rate is growing. Third, the more relative poverty rate (income inequality), increasing population aging rate, and elderly dependency ratio are high, elderly suicide rate goes high at the same time. Finally, this study proposed several socio-economic policy alternatives for preventing continuous growth of Korean elderly suicide rate. 본 연구는 노인자살증가의 원인을 파악하기 위해 거시적인 측면의 관점에서 노인자살률과 사회 경제적요인의 관련성을 분석하였다. 노인자살의 이론적 배경은 사회학적 관점과 경제학적 관점에 기초하여 설명하였다. 노인자살률의 경제적 요인에는 경제성장률과 실업률 그리고 노인의 경제활동참가율과 상대적 빈곤율(소득불평등율)을 포함하며, 사회적 요인의 범주에 속하는 변수로는 사회복지지출비, 이혼율, 그리고 고령화비 증가율과 노인부양비를 포함한다. 주요 연구결과로는 첫째, 노인의 경제활동참가율이 낮을수록 노인자살률이 높아지는 경향이 있었다. 둘째, 사회복지지출비가 낮을수록 노인자살률이 증가하는 것으로 나타났다. 셋째, 상대적 빈곤율, 고령화비 증가율, 그리고 노인부양비는 공히 이들이 증가할수록 노인자살률도 동시에 증가하는 것으로 나타났다. 끝으로 한국노인자살률의 지속적 증가를 예방하기 위해서 거시적 차원의 사회 경제적 정책방안을 제언하였다.